Student experiences of photovoice as a medium to inform decolonisation of the Health Sciences curriculum - Firoza Haffejee (University of Johannesburg, 2024)
Decolonisation of curricula embeds the African realities into teaching. Within the Health Sciences, learning, which is responsive to community health needs, is required. This study used photovoice, a student participatory teaching method, where students (n=96) engaged with local communities, capturing photographs of environmental factors involved in causing disease. Photographic information of local adverse environmental conditions was gathered, linking these to disease causation within local communities. This observation and analysis of the South African circumstances, particularly those of marginalized communities, emphasized local knowledge, which prepared students to work within their local and national contexts.  Students were prepared to be responsive to the needs of the people in their communities. This teaching pedagogy laid the foundation for lifelong learning as students were able to deal with real-life challenges while applying a new technology in the field of education. This will enable them to cope with changing aspects in health during their careers. Such changes are inevitable as population demographics and environments evolve with time. This alternate pedagogy, using photovoice, promoted decolonisation of the curriculum and has the potential to produce graduates who are reactive to local requirements of the community.